Istikhdamu Kitabu Al-Iktisyaf Li Tanmiyati Kafa’ati At-Tholabah Fi Maharati Qiro’ati Al-Kutubi At-Turos Li Al-fashli Al-Mubtadi’ Ma’had Manba’u Al-‘Ulum Sidomulyo Jember - Anugerah, Rizka; Firdausiyah, Nurul; Juharoh (Universitas KH. Mukhtar Syafaat, 2025)
The purpose of this study is to explain One of the effective methods to overcome students’ difficulties in reading yellow book (classical Islamic texts), despite their prior study of nahwu (syntax) and sharaf (morphology), is the Al-Iktisyaf method. This method was developed by KH. Abdul Hannan Tibyan and integrates three main books: Fath al-Qarib al-Mujib, Amtsilah Tashrifiyah, and Kitab al-Imrithi. The objectives of this study are To examine the implementation process of the Al-Iktisyaf method in teaching classical texts to beginner students at Ma’had Manba’ul ‘Ulum Sidomulyo Jember,and To evaluate the reading competence of beginner students in understanding classical texts and To identify the supporting and inhibiting factors in applying the Al-Iktisyaf strategy in teaching classical texts at the beginner level. The research approach used in this study is the qualitative approach, with a descriptive-analytical method. Data collection techniques include observation, interviews, and documentation.The results show that this method helps students improve their reading and comprehension skills more quickly and accurately. The method is implemented in three stages: explanation of vocabulary and rules, memorization and reading, and application of grammatical rules. Students’ competencies vary depending on their individual abilities, but enthusiasm and diligence are the key factors of success. Supporting factors include the availability of learning materials and motivation, while inhibiting factors include students’ lack of interest and challenges in creating a comfortable learning environment.